Single Nucleotide Polymorphism R25C and R25H on Leptin gene and their association with body weight and measurements of Pasundan cattle (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Hilmia N, Ramdani D, Hidayat R, Widyastuti R, Hernaman I, Dudi, Edianingsih P, Arifin J. 2023. Single Nucleotide Polymorphism R25C and R25H on Leptin gene and their association with body weight and measurements of Pasundan cattle. Biodiversitas 24: 6310-6315. The Leptin gene is a potential candidate for genetic selection in livestock. Nonsynonimous Single Nucleotide Polymorphisms (SNP) Arg25Cys/R25C in Leptin gene associated with fat deposition mainly. This study aimed to identify polymorphism of Leptin Gene based on SNPs of Pasundan cattle and their association with body weight and measurements. This research used 64 DNA samples along with the corresponding body weight and measurement data from Pasundan cattle. About 9 and 7 DNA samples from Bali and Ongole cross (PO) cattle respectively, were also collected as comparisons. The DNA along 620 bp was multiplied by PCR. The SNPs in the Leptin gene on exon two were identified, followed by direct sequencing of the PCR product. The sequencing results were analyzed by BioEdit and Molecular Evolutionary Genetic Analysis (MEGA) 4.0. The General Linear Model analyzed the association between SNPs and body weight and measurements. The results showed there were two nonsynonymous SNP in the Leptin gene on exon two, i.e. g.1047C>T/Arg25Cys/R25C (T allele) that changed amino acid Arginine to Cysteine and g.1048G>A/Arg25His/R25H (A allele) which changed Arginine to Histidine. The frequency of the C allele in the Leptin gene on Pasundan cattle (0.54) was higher than mutation alleles, i.e. T ( 0.29) and A allele (0.17). There were six genotypes: CC (0.266), CT (0.390), CA (0.156), TT, TA, and AA 0.063 respectively. The Leptin gene mutation at the 25th position of amino acids, which changed Arginin to Cystein or Histidin (R25C and R25H), did not affect body weight and measurement in Pasundan Cattle. Therefore, nonsynonymous SNP R25C and R25H could not be used as marker genetic selection in Pasundan cattle.